2018
DOI: 10.1002/med.21488
|View full text |Cite
|
Sign up to set email alerts
|

Targeting EGFRL858R/T790M and EGFRL858R/T790M/C797S resistance mutations in NSCLC: Current developments in medicinal chemistry

Abstract: Both the first-generation reversible epidermal growth factor receptor (EGFR) inhibitors gefitinib and erlotinib and the second-generation covalent epidermal growth factor receptor tyrosine kinase inhibitor (EGFR-TKI) afatinib have significantly improved the survival of non-small-cell lung cancer (NSCLC) patients with activating EGFR mutations. However, a secondary EGFR mutation leads to the clinically acquired resistance to the first- and second-generation EGFR-TKIs drugs. A number of the third-generation wild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(64 citation statements)
references
References 108 publications
0
62
0
Order By: Relevance
“…93 Additional examples of such combinations are available. 94,95 The concept of allosteric drug working conjointly with an orthosteric drug is not new. We only need to consider that a 'ligand' can be an orthosteric drug, with the allosteric drug acting to modulate it.…”
Section: (I) Allosteric Plus Orthosteric Drugsmentioning
confidence: 99%
“…93 Additional examples of such combinations are available. 94,95 The concept of allosteric drug working conjointly with an orthosteric drug is not new. We only need to consider that a 'ligand' can be an orthosteric drug, with the allosteric drug acting to modulate it.…”
Section: (I) Allosteric Plus Orthosteric Drugsmentioning
confidence: 99%
“…When R 1 was bromine, for aliphatic ring substitution of R 2 , it was found that compound with morpholinyl (22, 1.50 µM) had strong inhibition while piperidinyl (23) and piperazinyl (26) had no inhibition. For aromatic ring substitution of R 2 , compounds with phenyl (21) or pyridinyl (25) had no inhibition, while compounds of pyrimidinyl (20) and pyrazinyl (24) were active (0.44 and 0.69 µM, respectively). As can be seen, substituents R 2 had great influence on the inhibition of the triple mutant L858R/T790M/C797S EGFR tyrosine kinase.…”
Section: Resultsmentioning
confidence: 99%
“…The organic layer was separated and dried using anhydrous sodium sulfate, concentrated to afford a yellow solid 10.0 g, yield 66.8%, mp 116-118°C; 1 2-(5-Bromo-2-methoxyphenyl)-4-hydroxyquinazoline (3a): Intermediate 1 (20.0 g, 93.0 mmol) was dissolved in ethanol (60 mL), 2-aminobenzamide (12.7 g, 93.0 mmol) was added followed by iodine (26.0 g, 102 mmol). The reaction mixture stirred at reflux for 4 h. The reaction mixture was cooled to room temperature and quenched by 5% sodium thiosulfate solution, and extracted with dichloromethane for three times, the organic layer was separated and dried using anhydrous sodium sulfate, concentrated in vacuum, and the crude product was recrystallized from ethyl acetate to afford white solid 21 2-(5-Bromo-2-methoxyphenyl)-4-chloroquinazoline (4a): Com pound 3a (3.3 g, 10 mmol) was added to phosphorus oxychloride (10 mL), and then the reaction system was refluxed for 2 h, and then cooled to below 60°C. The phosphorus oxychloride was distilled under reduced pressure, and the mixture was cooled to room temperature.…”
Section: Synthesis Of Intermediates and Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent phase III study demonstrated that osimertinib was more effective as a first-line treatment compared to first-generation EGFR-TKIs in terms of PFS [ 115 ]. A recent study reported a tertiary C797S mutation as the cause of resistance to third-generation EGFR TKIs [ 116 ]. To overcome C797S, the development of fourth-generation EGFR inhibitors is highly desirable.…”
Section: Egfr Targeted Cancer Therapy Resistance and Overcoming Rementioning
confidence: 99%